The Relationship of Student’s Algrebraic Thinking and Cognitive Learning Style - Alip Rahmawati Zahrotun Nisak; Abdur Rahman As'ari; Rustanto Rahardi; S Subanji (IndoMath: Indonesia Mathematics Education, 2020)
This study aimed at investigating the relationship between student’s algebraic thinking and cognitive style of Field Independent (FI) and Field Dependent (FD). The method implemented in the study is Group Embedded Figure Test (GEFT) which was intended to categorize students into the FI and FD styles. Afterward, to collect the data of students’ algebra thinking ability, a test was administered. The result of the test was compared to the result of GEFT test by integrating a computer program to find out the relationship between the students’ algebraic thinking and their cognitive styles, both FD and FI. The subjects of this research were the eighth-grade students totaling at 24 students. The findings of this study indicate that there is no relationship between manipulating symbols and students’ cognitive style.. There is a relationship between generalizing and formalizing and stundents’ cognitive styles. There is a relationship between using algebra as a tool and FD. There is a relationship between reasoning and representation and student’s cognitive style.